A Systematic Literature Review: The Influence of Compensation and Motivation on Employees Performance - Tanjung, Suci Rahmadani; Rahayu, Esty Budi; Dalimunthe, Ritha F.; Lumbanraja, Prihatin (PT FORMOSA CENDEKIA GLOBAL, 2025)
Employees are the most important asset in the company. Fair compensation and high work motivation are believed to be able to increase employee productivity and work quality in an organization, so that employees' abilities can provide their best performance to the company. Compensation and employee performance are two things that are interconnected. Where the more compensation an employee receives, either directly or indirectly in the company. So you could say that compensation and performance have a directly proportional relationship. If employees receive compensation in increasing amounts, it will increase maximum performance for the company. The method used in this study is Systematic Literatur Review. The articles that used for reference from Google Scholar, with publication times 2020-2025. From the research that has been conducted by researchers, it can be concluded that there is an impact from compensation variables and motivation variables in company performance, because with compensation and motivation employees will feel more active and enthusiastic on improving company performance.